Posthaste Outgrow of Lip Pyogenic Granuloma after Diode Laser Removal - Asnaashari, Mohammad; Bigom -Taheri, Jamile; Mehdipoor, Maesoome; Bakhshi, Mahin; Azari-Marhabi, Saranaz (Journal of Lasers in Medical Sciences, 2014)
Introduction: Pyogenic granuloma (PG) is one of the inflammatory hyperplasia seen in the oral cavity. It is a reactional response to minor trauma or chronic irritation and also might be related to hormonal changes. Rarely, PG occurs extragingivally.The most common treatment of PG is surgical excision but alternative approaches such as laser excision have also been proposed. Case report: Herein, we present a case of lip pyogenic granuloma in a 15-year-old male whom had been under orthodontic treatment. The lesion was first excised with diode laser as a conservative method, but the lesion had immediately recurred and was excised with surgical blade as the traditional method. No recurrence or scarring was observed in 6 months follow-up. Results and conclusion: Although the use of laser as modern medicine offers a new tool for treatment of oral lesions, scalpel (blade) surgical excision still seems to be the successful treatment of choice in minimizing the recurrence of lesion especially when exacerbating factors such as hormonal imbalances exist.